About preconditions of creating a unified electronic platform for the professional development of personnel (Journal of actual problems of jurisprudence, 2021)
This article discusses the preconditions of creating a unified electronic platform for the professional development of personnel in 2020, which arose as a result of the fight against a new threat to all mankind – the COVID-19 coronavirus pandemic. The main direction of the research is to study the possibility of personnel improving their skills remotely. The practical significance of the work is expressed in the justification that recognition in national legislation governing the training opportunities through the use of a unified electronic platform, will serve as a tool to achieve the objectives of the national plan and strategy of development of Kazakhstan in the sphere of the human capital development and digitalization . The research used methods of studying and analyzing specialized literature, regulatory legal acts, national statistics, comparing national legislation and the legislation of the Eurasian Economic Union countries, together with a compiled SWOT analysis. The article analyzes the national experience in the development of the institute for the arrangement of services in electronic form. The authors highlight the strengths and weaknesses of the implementation of the proficient improvement prepare through the utilize of a unified electronic platform. The authors conclude that the creation of such a platform will lead to positive results in the development and modernization of labor relations and relations directly related to labor relations. The materials of the article can be used by interested persons associated with the work in the field of development of the institute for improving the qualification of personnel, and also within the field of digitalization of educational services.Key words: labor relations, professional development, e-learning, education.